Apoptosis-promoted tumorigenesis: γ-irradiation-induced thymic lymphomagenesis requires Puma-driven leukocyte death - Michalak, Ewa M. (Cold Spring Harbor Laboratory Press, 2010)
Although tumor development requires impaired apoptosis, we describe a novel paradigm of apoptosis-dependent tumorigenesis. Because DNA damage triggers apoptosis through p53-mediated induction of BH3-only proteins Puma and Noxa, we explored their roles in γ-radiation-induced thymic lymphomagenesis. Surprisingly, whereas Noxa loss accelerated it, Puma loss ablated tumorigenesis. Tumor suppression by Puma deficiency reflected its protection of leukocytes from γ-irradiation-induced death, because their glucocorticoid-mediated decimation in Puma-deficient mice activated cycling of stem/progenitor cells and restored thymic lymphomagenesis. Our demonstration that cycles of cell attrition and repopulation by stem/progenitor cells can drive tumorigenesis has parallels in human cancers, such as therapy-induced malignancies.